Evaluation of an anatomic definition of non-aneurysmal perimesencephalic subarachnhoid hemorrhage. (23rd March 2015) - Wallace, Adam N; Vyhmeister, Ross; Dines, Jeffrey N; Chatterjee, Arindam R; Kansagra, Akash P; Viets, Ryan; Whisenant, Justin T; Moran, Christopher J; Cross, DeWitte T; Derdeyn, Colin P
Abstract : Background and purpose: Perimesencephalic subarachnoid hemorrhage (PSAH) is not consistently defined in the existing literature. The purpose of this study was to test the inter-observer variability and specificity for non-aneurysmal subarachnoid hemorrhage (SAH) of an anatomic definition of PSAH. Methods: Medical records of all patients who underwent catheter angiography for evaluation of non-traumatic SAH between July 2002 and April 2012 were reviewed. Patients with anterior circulation aneurysms were excluded. Three blinded reviewers assessed whether each admission CT scan met the following anatomic criteria for PSAH: (1) center of bleeding located immediately anterior and in contact with the brainstem in the prepontine, interpeduncular, or posterior suprasellar cistern; (2) blood limited to the prepontine, interpeduncular, suprasellar, crural, ambient, and/or quadrigeminal cisterns and/or cisterna magna; (3) no extension of blood into the Sylvian or interhemispheric fissures; (4) intraventricular blood limited to incomplete filling of the fourth ventricle and occipital horns of the lateral ventricles (ie, consistent with reflux); (5) no intraparenchymal blood. Results: 56 patients with non-aneurysmal SAH and 50 patients with posterior circulation or posterior communicating artery aneurysms were identified. Seventeen (16%) of the 106 admission CT scans met the anatomic criteria for PSAH. No aneurysm was identified in this subgroup. Inter-observer agreement was excellent with κ scores of 0.89–0.96 and disagreement in 2.8% (3/106) of cases. Conclusions: Our anatomic definition of PSAH correlated with a low risk of brain aneurysm and was applied with excellent inter-observer agreement.